Effectiveness of Schema Therapy on Emotion Regulation and Anxiety Sensitivity in Women with Borderline Personality Disorder - Pakdel Sabzgol , Sima; Hasani , Masoumeh; Ahangaran, Alireza (Psychology of Woman Journal, 2026)
Objective: The present study aimed to examine the effectiveness of schema therapy on emotion regulation and anxiety sensitivity in women with borderline personality disorder.Methods and Materials: This study employed a quasi-experimental design with a pretest–posttest and a two-month follow-up with a control group. The statistical population consisted of women diagnosed with borderline personality disorder who attended a specialized psychology clinic in Tehran in 2025. A total of 30 participants were selected using convenience sampling and randomly assigned to experimental (n = 15) and control (n = 15) groups. The experimental group received schema therapy intervention over ten 90-minute sessions, while the control group received no intervention. Data were collected using the Difficulties in Emotion Regulation Scale and the Anxiety Sensitivity Questionnaire. Data analysis was conducted using two-way repeated measures analysis of variance in SPSS-26.Findings: The results indicated that there were significant differences between the experimental and control groups in emotion regulation (p = 0.024) and anxiety sensitivity (p = 0.008). Additionally, within-group (time) effects were significant for both emotion regulation (p < 0.001) and anxiety sensitivity (p < 0.001). The interaction effect of group and time was also significant for emotion regulation (p < 0.001) and anxiety sensitivity (p < 0.001), indicating that schema therapy significantly improved emotion regulation and reduced anxiety sensitivity in the experimental group compared to the control group, with effects maintained at follow-up.Conclusion: The findings suggest that schema therapy is an effective intervention for enhancing emotion regulation and reducing anxiety sensitivity in women with borderline personality disorder, and its effects are stable over time. Therefore, schema therapy can be recommended as a therapeutic approach for improving emotional and psychological functioning in this population.